Korczaka i współczesnych pedagogów ulicy koncepcja uwspólniania świata jako inspiracja podejść partycypacyjno-rozwojowych w pracy z dziećmi ulicy - Jolanta Sokołowska (Problemy Wczesnej Edukacji)
Janusz Korczak has his unique contribution to the development of work with street children. The purpose of this text is an attempt to answer the question: what has Korczak in common with people who are working with the category of abandoned, neglected children nowadays? To what extent his views, developed over a hundred years ago, are an inspiration for educators taking up work in the street space today? To answer these questions I will refer both to Korczak’s thoughts contained in his works as well as to the texts created by contemporary educators. The analyses confirm that the common feature of the described projects is the concept of sharing the world. Both Korczak and pedagogues of the street situate themselves close to the children’s community, participating in their everyday life. Both pedagogues and Korczak refer to a similar concept of the child, focusing primarily on the child’s potential. They try to get to know the child’s living conditions and by understanding its habitus they aim to take actions appropriate to child’s abilities, avoiding elements of symbolic violence.